Hitler's ghettos : voices from a beleaguered society, 1939 - 1944 - Corni, Gustavo 1952- (Arnold, 2003)
Witnesses from the ghettos : an analysis of the sources -- The construction of the ghettos -- The reaction of the Jews to ghettoization -- The Judenräte -- The Jewish police -- Life in the ghettos -- Ghetto society : all equal? -- Life and death -- Work as salvation -- Round-ups, deportations and the elimination of the ghettos -- Resistance in the ghettos -- Conclusion : morality besieged